Margarita Mendizábal, Social Housing and Participation: Two Projects in Madrid - Ocerin-Ibáñez, Olatz (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The following article exposes two collective social housing projects carried out in Madrid by the architect Margarita Mendizábal Aracama. They are two projects of twenty-four and one hundred and nine homes carried out in 1969 and 1978, respectively, that stand out for incorporating participatory architecture into their design process. This unique project method, unusual in architectural practice in Spain, allowed us to reflect both the housing demands of future users and the symbolic function that the architecture of their homes had to adopt. Despite being located in two paradigmatic areas of Madrid such as Moratalaz (developed by the Obra Sindical del Hogar) and the ACTUR of Tres Cantos and having been carried out by one of the architects pioneers of Spain, their modest character and their contained dimensions have gone unnoticed by historiography. The objectives of the text are, on the one hand, to reflect the historical value of the participatory project and its application in these two collective social housing projects; and, on the other hand, to publicize the work of Margarita Mendizábal, to contribute to expanding knowledge about architecture and architectural culture in Spain.